(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
The study aims to identify the position of the tribes and leaders of Palestines’ Jund towards the Umayyad Caliphate characterized by fluctuation between loyalty and rebellion caused by the leaders’ self-interests. Their attitude towards the successors of Banu Umayyads after being replaced by the Marwanids was linked to the caliph’s ability to manage state affairs. The study highlights Natil Ibn Qays’s abandonment of some of the successors of Banu Umayyad, the support of the Jund tribes for the rebellion of the tribes of the Levant, and the role of Thabit ibn Na’im and the offspring of Rawh Ibn Zinba in participating in the rebellion movements, which influenced the rapid deterioration of the Umayyad state.